PENINGKATAN AKTIVITAS BELAJAR MURID DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN MIND MAPPING DI SEKOLAH DASAR - Fitriyani, Devi; Halidjah, Siti; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractMind mapping is a creative way for each student to generate ideas, record what they learn, or plan new tasks. This study aims to improve student learning activities using mind mapping model.This research uses descriptive method, with form of action research class (PTK), and is collaborative. The subjects of this study were teachers and students of class V which amounted to 20 students. This research was conducted in odd semester at class V SDN 07 Pontianak Kota. The procedure used there are 4 stages, namely the planning stage, implementation stage, stage of observation, and reflection. Technique used in this research is observation and observation of document by means of data collector is observation sheet and document observation sheet. Data analysis in this research was conducted between researcher and observer collaboration.The result of the research is to increase the students' learning activity using mind mapping model in cycle 1 which is obtained by 35.12%, in cycle 2 it has increased by 18.45% to 53.57%, in cycle 3 has increased by 17.26% to 70 , 83%, and in cycle 4 also increased by 11.91% to 82.74%. With the implementation of mind mapping model on Citizenship Education can improve student learning activities. It can be concluded that the use of mind mapping model can improve student learning activity in learning Citizenship Education in class V Elementary School 07 Pontianak City.Keywords: Improvement, Learning Activity, Mind Mapping